2002
DOI: 10.1046/j.1526-4610.2002.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Headaches in Adolescents: A Five‐Year Follow‐Up Study

Abstract: Our data indicate that juvenile-onset MWOA and MD may change in character over time, generally with a favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
72
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 17 publications
19
72
5
Order By: Relevance
“…It was reported in a study that migraine usually develops in childhood, adolescence or adulthood 11 . In a study 12 it was also reported that headache intensity declined from 40 years to 74 years with change in headache frequency or duration which is consistent with this study and also consistent with the previous study done in Bangladeshi population 13 .…”
Section: Discussionsupporting
confidence: 92%
“…It was reported in a study that migraine usually develops in childhood, adolescence or adulthood 11 . In a study 12 it was also reported that headache intensity declined from 40 years to 74 years with change in headache frequency or duration which is consistent with this study and also consistent with the previous study done in Bangladeshi population 13 .…”
Section: Discussionsupporting
confidence: 92%
“…The increase in prevalence of neck pain and/or headache with a female sex shift in adolescence has been noted previously in the literature. 5,14,19,23,27,28,76,77 Students in this study reported having a fairly high level of pain and that it affected some students in their ability to participate in daily activities. Twenty percent reported that they have pain 1 to 2 times a week.…”
Section: Discussionmentioning
confidence: 74%
“…17,18 This is reflected in the wide range of prevalence rates quoted in studies: they are from as low as 6% to as high as 80%. 16,[19][20][21][22][23][24][25][26][27][28] Almost all of the information obtained from studies of neck pain and/or headache in children comes from questionnaires, but the validity of assessing pain retrospectively in children has been disputed. [29][30][31] Age appropriate daily pain diaries have been found to be most accurate in assessing the duration, intensity and frequency of pain in children.…”
mentioning
confidence: 99%
“…10 In a study of 11-to 14 year-old migraine sufferers (n ¼ 42), the 10-year rates were 36%, 38%, and 23%, respectively 18 ; the 5-year rates were 28% (headache-free) and 56% (persistent migraine). 12 Migraine prevalence seems to decrease gradually over time to a level that nevertheless remains high. Reported rates are 60%, 56%, 49%, 45%, 38%-55%, 49%, and 54% at 3, 5, 6, 8, 10, 20, and 40 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] In 12%-30% of patients, headache intensity decreases. [9][10][11][12][13][14][15][16][17][18] Factors associated with a worse prognosis are female gender, time between attack onset, and its management, family history of migraine, onset before 6 years of age, and attack intensity. [9][10][11]13,18,20,21 The objective of this study was to evaluate long-term prognosis 10 years after diagnosis in a population of children and adolescents with migraine.…”
Section: Introductionmentioning
confidence: 99%